MULTIKULTURAL PERSPEKTIF SOSIOLOGIS - Nofal Liata; Khairil Fazal (Abrahamic Religions: Jurnal Studi Agama-Agama, 2021)
This study discusses the concept of a multicultural society in a sociological perspective, where the Indonesian state as a gathering place for various ethnic groups, nations, religions and beliefs in its history has provided valuable lessons. There are times when diversity in Indonesia creates conflict, but in other places there is also the diversity that is owned by the Indonesian people as a source of strength to keep each other from being crushed by the progress of the times. Understanding multiculturalism is not something that must be owned by intellectuals or those from community leaders only, but all levels, layers, and lines of society become a necessity for the importance of understanding this multiculturalism. Because at this time the reality is that Indonesian people in general are very vulnerable to disaster due to SARA (ethnic, religion, race, and inter-group) issues that are blown by electronic media. In order to prevent "bloody conflict" disasters from happening again, multiculturalism will always be relevant to be discussed throughout the ages, considering that generations are always changing. The purpose of this study is to bring the understanding of multiculturalism in particular to the younger generation, and in general at all levels of society, not just an academic discourse. The method in writing this work uses library research, as well as by presenting examples of cases that have occurred in Indonesia. The results of the study in the discussion chapter, in general it can be concluded that the understanding of multiculturalism in Indonesia is not something that comes from outside, meaning that local wisdom created from ancient times has also strengthened the conditions of multicultural society. But on the other hand, unequal access to education by the community until now, the potential for horizontal conflict is always there. In the context of the consequences of a pluralistic society in Indonesia, that within a diverse structure, the seeds of conflict at times become a latent threat to damage the social order. And problems at the local level will easily become national problems because there are no longer limits for people to consume information